Stability Analysis of Fractional-Order Predator-Prey System with Square Root Functional Response - Karthikeyan, S.; Ramesh, P.; Sambath, M.; Balachandran, K. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this work, the dynamics of a fractional-order predator-prey system with nonlinear prey harvesting and square root type functional response for prey herd behavior is proposed and analyzed. We establish the existence, uniqueness, non-negativity, and boundedness of the solutions for the proposed model. We study the stability of each equilibrium point in the system as well as the conditions under which each equilibria occur. Additionally, the global stability of the co-existence equilibrium point is examined using a suitable Lyapunov function. To show the consistency of the theoretical method, we conclude with numerical simulations.